(untitled) (Research, Society and Development, 2025)
Trauma is caused by external forces, such as accidents or violence, and polytrauma refers to the occurrence of multiple simultaneous injuries. Proper initial assessment, guided by structured protocols, is essential for the prognosis of polytraumatized patients. This study aims to identify the main factors that influence the care of polytraumatized patients in emergency settings through an integrative literature review. The research was conducted on the Regional Portal of the Virtual Health Library, using specific health-related descriptors such as emergency medical and hospital services, patient care teams, and multiple trauma. Publications from January 2019 to March 2024 were included, with data collection carried out in March and April 2024, in compliance with current copyright legislation. Initially, 709 publications were identified, from which 13 articles were selected after refinement. Data analysis was conducted using cataloging forms, flowcharts, and tables, resulting in four thematic categories: sociodemographic characteristics of patients, injury mechanisms, types of injuries and complications, and initial assessment and clinical management. The results showed that age, gender, and injury mechanism directly influence complications and types of injuries. Early assessment and proper management proved to be crucial for survival, highlighting the importance of standardized protocols and continuous team training. The adoption of evidence-based practices and ongoing professional development are essential to improve care and reduce morbidity and mortality in polytrauma cases.